The value of
k = 0 ∑ 9 9 7 k 3 + 9 k 2 + 2 6 k + 2 4 ( − 1 ) k ( k 9 9 7 )
Can be expressed in the form n m . Where m and n are coprime positive integers, find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Does anyone have a link to a website or pdf detailing how to manipulate permutation sums?
Done the same way.
I did it the same way. Nice solution. @Sean Ty
so simple...
How did you arrive with 2nd Expression?
Problem Loading...
Note Loading...
Set Loading...
We will prove a more general case.
We have k = 0 ∑ n ( k + 2 ) ( k + 3 ) ( k + 4 ) ( − 1 ) k ( k n ) = k = 0 ∑ n ( − 1 ) k ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) k + 1 ( k + 4 n + 4 ) = ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) 1 k = 4 ∑ n + 4 ( − 1 ) k ( k − 3 ) ( k n + 4 )
So now we only have to calculate k = 4 ∑ n + 4 ( − 1 ) k ( k − 3 ) ( k n + 4 )
Note that k = 4 ∑ n + 4 ( − 1 ) k ( k − 3 ) ( k n + 4 ) = k = 4 ∑ n + 4 ( − 1 ) k k ( k n + 4 ) − 3 k = 4 ∑ n + 4 ( − 1 ) k ( k n + 4 ) = n + 4 1 k = 1 ∑ n + 4 ( − 1 ) k ( k − 1 n + 3 ) = 0
Thus,
k = 4 ∑ n + 4 ( − 1 ) k ( k − 3 ) ( k n + 4 ) = − k = 0 ∑ 3 ( − 1 ) k ( k − 3 ) ( k n + 4 ) = 2 ( n + 1 ) ( n + 2 )
And the sum we seek is then ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) 1 × 2 ( n + 1 ) ( n + 2 ) = 2 ( n + 3 ) ( n + 4 ) 1
Substituting n = 9 9 7 , we will arrive with the answer 2 0 0 2 0 0 0 1 , and m + n = 2 0 0 2 0 0 1